Bird Strike Risk Assessment to Support Flight Safety: A Case Study at Kalimarau Airport - FRIENDY GIVENUS MARPAUNG; Dwi Afriyanto; Alwazir Abdusshomad (FTK UNSURYA, 2026)
Bird strikes pose a serious threat to aviation safety, especially at airports surrounded by natural habitats that attract birds. This study aims to identify bird species with the highest risk to aviation safety at Kalimarau Airport, Berau, and provide mitigation recommendations based on risk analysis results. The method used is a descriptive quantitative approach with risk assessment techniques using the Sowden and MOORA methods. The results of the study show that the species Egretta garzetta (little egret) has the highest score in both assessment methods, thus categorized as the species with the highest bird strike risk. This is due to the birds' gregarious behavior, low-flying habits, and the airport's surrounding habitat, which provides natural food sources and shelter. The conclusions of this study support the hypothesis that there are bird species with high bird strike risk at Kalimarau Airport. Comprehensive habitat management and the use of early detection technology are necessary as strategic measures to reduce the potential for bird strike incidents.